Major Production Constraints and Spider Plant [Gynandropsis gynandra (L.) Briq.] Traits Preferences Amongst Smallholder Farmers of Northern Namibia and Central Malawi - Chataika, Barthlomew Yonas; Akundabweni, Levi Shadeya-Mudogo; Sibiya, Julia; Achigan-Dako, Enoch G.; Sogbohossou, Dêêdi E. O.; Kwapata, Kingdom; Awala, Simon (Frontiers in Sustainable Food Systems, 2022)
Spider plant (Gynandropsis gynandra (L.) Briq) is among the most important African Leafy Vegetables (ALVs) as a source of essential nutrients with the potential of contributing significantly to household food and nutritional security and mitigation of hidden hunger. Nevertheless, the vegetable is considered an orphan crop, and its production is challenged by inadequate research to identify and improve traits preferred by smallholder farmers. The research was conducted to identify the main challenges impacting the production of spider plants and identify traits preferred by smallholder farmers in northern Namibia and central Malawi for use in demand-led crop improvement. Semi-structured interviews involving a random selection of 197 farming households from five regions of northern Namibia and three districts of central Malawi were conducted. In addition, six key informant interviews and four focus group discussions were conducted to triangulate the findings. Data were analyzed using IBM SPSS version 20. Fischer’s exact test was used to test for independence in the ranking of production constraints and agronomic traits, while Kendall’s Coefficient of Concordance (W) was used to measure agreement levels in the ranking across the countries. Farmers indicated lack of seed, poor soil fertility, poor seed germination, and drought as the main production challenges across the two countries. Production constraints were ranked differently (p<0.001) across the study sites suggesting the influence of biophysical and socio-economic factors associated with production. High yield and drought tolerance were considered the most important agronomic traits among the smallholder farmers in both countries. The findings of this study are useful for designing demand-driven pre-breeding trials that prioritize the needs of the end-users. Demand-led breeding has the potential to stimulate the production and utilization of spider plant, hence contributing to household food and nutritional security.